Maintain and increase vaccination coverage in children, adolescents, adults and elderly people: Let's avoid adding epidemics to the pandemic: Appeal from the Board of the Vaccination Calendar for Life in Italy: Maintain and increase coverage also by re-organizing vaccination services and reassuring the population. Issue 8 (22nd February 2021) - Bonanni, P.; Angelillo, I.F.; Villani, A.; Biasci, P.; Scotti, S.; Russo, R.; Maio, T.; Vitali Rosati, G.; Barretta, M.; Bozzola, E.; Castiglia, P.; Chiamenti, G.; et al.
Abstract: The Board of the Vaccination Calendar for Life (Bonanni et al., 2014, 2017) [1, 2] ), a coalition of four major scientific and professional societies of public health physicians, pediatricians and general practitioners in Italy, made an appeal to health authorities in order to sustain vaccination in COVID-19 times. The five pillars to maintain and increase vaccination coverage at all ages are described as follows: 1) Guarantee paediatric vaccination coverage to all newborns and paediatric boosters and adolescent immunizations, not interrupting active calls and scheduled sessions. 2) Re-organise the way paediatric and adolescent vaccinations are offered. 3) Set-up recovery programs for vaccinations not carried out after the start of the COVID-19 emergency. 4) Provide the preparation of tenders for the supply of flu vaccines with suitable quantities to increase coverage in all Regions and Autonomous Provinces with extreme urgency. 5) Prepare plans to increase coverage for influenza, pneumococcal, tetanus diphtheria and shingles. The Board of the Calendar for Life appeals to the National and Local Health Authorities for a strong and coordinated commitment in favor of the widest offer and acceptance of vaccinations, whose vital importance for collective health is now even more evident to all, in order to avoid that delays in the necessary initiatives should add damage from other epidemics to those suffered by our population due to the COVID-19 pandemic.